Theoretical and Experimental Comparison of Micro-hardness and Bulk Modulus of Orthorhombic YBa2Cu3-xZnxO Superconductor Nanoparticles Manufactured using Sol-Gel Method - AŞIKUZUN, Elif; ÖZTÜRK, Özgür (Sakarya University Journal of Science, 2020)
In the present study, the sol-gel method was preferred for the production of superconductor materials since it is known that the sol-gel method is useful in producing nanoparticles. The Zn (Zinc) doped YBCO-123 superconductor samples (YBa2Cu3-xZnxO) were produced. The main objective in the present study was to examine the effects of both of Zn doping and sol-gel method, which was chosen as the production method, on the structural, electrical, and mechanical properties of Y-123 superconductor materials. Especially, the effects of the nanoparticles and doping on the mechanical properties of materials were discussed over the bulk modulus. It was aimed to obtain information about the mechanical properties by comparing the bulk modules calculated theoretically and experimentally. Besides that, the XRD, SEM, and resistivity measurements were performed in order to characterize the structural and electrical properties.
Keywords: vickers; Chemistry; bulk modulu; Metrology, Applied and Industrial Physics; sol-gel; micro-hardness; Sol-gel; vickers; bulk modulu; micro-hardness; TA1-2040; Metroloji,Uygulamalı ve Endüstriyel Fizik; Engineering (General). Civil engineering (General); QD1-999